Corneal Ulcer in a Sheep - Treatment with Third Eyelid Flap - Lopes, Jaine Mendes; Brito, Lucas Dourado; Melo, Danilo Rocha de; Costa, Ana Karoline Rodrigues da; Veloso, Jessica Fontes; Carlos, Renata Santiago Alberto; Gomes Junior, Deusdete Conceição (Acta Scientiae Veterinariae, 2022)
Background: Corneal ulcers are frequently reported in the literature in several species, however, the treatment of traumatic lesions on the corneal surface of ruminants is still poorly described. The use of the third eyelid flap is questioned when applied to deep ulcers, since the technique prevents the evolutionary follow-up of corneal healing and compromises care. However, several authors report its successful use for the treatment of superficial and deep corneal ulcers. This technique protects the ocular surface and prevents the occurrence of new lesions or their aggravation. The aim of this study was to report the treatment of corneal ulcers in sheep through the third eyelid flap associated with the use of topical antibiotics. Case: A 2-year-old Dorper sheep, with ocular discomfort, conjunctival hyperemia and mucopurulent secretion in the left eye, was assisted in a private rural property in the West region of Bahia, Brazil. The owner reported that before seeking veterinary help he used a spray based on oxytetracycline and hydrocortisone, which worsened the animal’s condition. Upon inspection, it was observed eyelid asymmetry, slight lateralization of the head to the left, periorbital alopecia on the left face, intense blepharospasm in the left eye, with projection of the third eyelid occurring at times. The ophthalmic examination was performed after application of anesthetic eye drops based on proxymetacaine to reduce eye discomfort. A corneal stromal lesion, edema and fibrovascular tissue in the left eye were identified, but the cause of the lesion was not defined, with lagophthalmia, entropion, dystychiasis or ectopic cilia being ruled out. So, it was suggested that the lesion had occurred by a foreign body, such as dust or feed fiber. The contralateral eye showed no changes, Schirmer 15 mm, no changes in sensory and sensory reflexes and negative fluorescein. No signal clinical disease. Due to the severity of the lesion, it was performed a third eyelid flap associated with drug treatment with ciprofloxacin eye drops, every 8 h for 21 days. The animal was placed in the right lateral decubitus position and palpebral akinesia was achieved with the application of 2 mL lidocaine without vasoconstrictor in the region of the auriculopalpebral nerve. This was followed by the routine performance of the third eyelid flap. Discussion: The delay in seeking veterinary care and the application of spray based on oxytetracycline and hydrocortisone aggravated the lesion, since the corticosteroid delays corneal healing and favors the aggravation of the lesion. After desensitization of the cornea, the animal allowed eye manipulation and it was possible to observe the lesion and choose the best treatment, with option for the third eyelid flap because it is a simple and fast technique, does not require special equipment or materials, ideal for performed in the field and is widely used in the treatment of injuries involving the cornea and, besides that, helps to contain corneal perforation and protect the ocular surface. Corneal debridement was also performed to remove necrotic debris and improve drug action, in addition to using broad-spectrum antibiotic eye drops until complete regeneration of the lesion. Twenty-one days after the surgical procedure, the patient had no ocular discomfort, the flap was removed and no changes in the corneal surface were observed. The treatment was considered satisfactory for the healing of the corneal ulcer, guaranteed the esthetics and visual function of the sheep. Keywords: keratitis, surgery, ciprofloxacin, ocular, ruminant.